2019
DOI: 10.1016/j.ebiom.2019.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Low TREM1 expression in whole blood predicts anti-TNF response in inflammatory bowel disease

Abstract: BackgroundWith the changed therapeutic armamentarium for Crohn's disease (CD) and ulcerative colitis (UC), biomarkers predicting treatment response are urgently needed. We studied whole blood and mucosal expression of genes previously reported to predict outcome to anti-TNF therapy, and investigated if the signature was specific for anti-TNF agents.MethodsWe prospectively included 54 active IBD patients (24CD, 30UC) initiating anti-TNF therapy, as well as 22 CD patients initiating ustekinumab and 51 patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
122
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 31 publications
2
122
2
2
Order By: Relevance
“…In humans, TREM-1 + Mfs are increased in IBD patients and its engagement enhanced pro-inflammatory cytokine secretion while a TREM-1 antagonist dampened it (254,255). Finally, Verstockt et al have shown that low TREM-1 expression in both whole blood and intestinal mucosa can predict anti-TNF therapy responders (353,354). Thus, TREM-1 could be a potential biomarker for predicting the effect of anti-TNF therapy and, secondly, blocking TREM-1 could be an attractive target for IBD treatment.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…In humans, TREM-1 + Mfs are increased in IBD patients and its engagement enhanced pro-inflammatory cytokine secretion while a TREM-1 antagonist dampened it (254,255). Finally, Verstockt et al have shown that low TREM-1 expression in both whole blood and intestinal mucosa can predict anti-TNF therapy responders (353,354). Thus, TREM-1 could be a potential biomarker for predicting the effect of anti-TNF therapy and, secondly, blocking TREM-1 could be an attractive target for IBD treatment.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…Several mucosal biomarkers have been reported to be associated with response to anti-TNF agents in CD: oncostatin M, 15 TNFR2 and IL13RA2, 16,17 and TREM1. 18,19 For example, high pretreatment levels of transmembrane TNF positive cells were observed to be positively associated with response to adalimumab, 22 whereas high pre-treatment levels of oncostatin M were found to be negatively associated with response to infliximab and goliumumab. 19 With respect to predicting response to anti-integrin therapy, high mucosal gene expressions of α E 23 and granzyme A 24 were demonstrated to be associated with improved response to etrolizumab in patients with UC.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal and blood biomarkers that can predict responses to anti-TNFs using the multi-omics approach include oncostatin M, 15 TNFR2 and IL13RA2, 16,17 and TREM1. 18,19 However, integrating them into routine clinical care has not yet occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The cost reductions, now being seen with the availability of biosimilars, will further improve the cost‐effectiveness of this class . Finally, the identification of predictive biomarkers may lead to a more personalised approach to the use of these agents …”
mentioning
confidence: 99%
“…9 Finally, the identification of predictive biomarkers may lead to a more personalised approach to the use of these agents. 10 Improvements in IBD outcomes over a decade may have many causes. It is essential that we continue to look to improve outcomes not only through the use of new pharmaceutical agents but also through improving the services we provide to our patients.…”
mentioning
confidence: 99%